If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -5y = 12 + -6y Solving 11 + -5y = 12 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 11 + -5y + 6y = 12 + -6y + 6y Combine like terms: -5y + 6y = 1y 11 + 1y = 12 + -6y + 6y Combine like terms: -6y + 6y = 0 11 + 1y = 12 + 0 11 + 1y = 12 Add '-11' to each side of the equation. 11 + -11 + 1y = 12 + -11 Combine like terms: 11 + -11 = 0 0 + 1y = 12 + -11 1y = 12 + -11 Combine like terms: 12 + -11 = 1 1y = 1 Divide each side by '1'. y = 1 Simplifying y = 1
| -x(0)+26y= | | -x+26y= | | 8+6m=5m | | 752=4(x+19) | | FV=1000(1+0.02)12 | | 12-12+7= | | 24x=180n-360 | | 8+6m=5 | | y=-2x^2+6 | | x^2-6x+9x=0 | | 3+6-16= | | 2-5x=x+14 | | 8w=9+5w | | 7n+2(2n-4)-2= | | 3y+2(2y-3)=8-7(y-2) | | 7x-10=11x+6 | | 3c=-8+5c | | -12=3x-7 | | 0.45x+0.33=0.66 | | (8y-17)=(6y+5) | | (a*5)*6a= | | 9+1x=3+7 | | -6+4T=3t | | 12-(4m+7)=3+2m-16 | | -0.2(6.5n-2)=0.848 | | -3=x/12 | | (12y-y)=11 | | 4(5-2y)=2(1-y) | | 0=-3x^3-3x^2+168x | | -3-7x=-66 | | -3-7=-66 | | y=7-7x |